1974
DOI: 10.1177/0145482x7406801001
|View full text |Cite
|
Sign up to set email alerts
|

Manpower Needs in Orientation and Mobility

Abstract: This survey of the current status of the specialized field of orientation and mobility instruction—based on 317 questionnaires returned by the administrators of agencies and schools serving blind persons, day-school programs, hospitals, and residential schools for other handicapped persons—collected data on the number of specialists employed, the present and future need for specialists, desired level of training, starting salaries, and other duties. The authors conclude that because of the current and expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 0 publications
0
20
0
3
Order By: Relevance
“…O estudo mostra que a percepção e avaliação que os alunos têm de si próprio formase por meio da prática do JO em situações de interação com o professor, permitindo às crianças e adolescentes cegos perceberem a sua competência e compará-la com a dos outros, de acordo com Welsh & Blasch (1980), Novaes (1985) e Goffman (1988) Pode-se afirmar que, quanto mais profundo for o conhecimento que o sujeito tem acerca da sua competência, mais fácil se torna a autoavaliação de suas potencialidades e seus limites, logo mais fácil se torna a mudança e o reconhecimento do seu valor pessoal: quanto mais se conhece a si mesmo, mais se olha para dentro de si, assim ao se olhar para dentro de si, fica fácil se colocar no lugar do outro. Ao fazer esse exercício, comete-se menos erro, portanto, a autoavaliação torna-se relevante por auxiliar o indivíduo na compreensão de si mesmo e na identificação das relações que mantém com as ações afetivas; quanto mais se liga ao mundo, melhor será a forma de se perceber como parte dele, ampliando sua visão de mundo e sociedade.…”
Section: Discussionunclassified
“…O estudo mostra que a percepção e avaliação que os alunos têm de si próprio formase por meio da prática do JO em situações de interação com o professor, permitindo às crianças e adolescentes cegos perceberem a sua competência e compará-la com a dos outros, de acordo com Welsh & Blasch (1980), Novaes (1985) e Goffman (1988) Pode-se afirmar que, quanto mais profundo for o conhecimento que o sujeito tem acerca da sua competência, mais fácil se torna a autoavaliação de suas potencialidades e seus limites, logo mais fácil se torna a mudança e o reconhecimento do seu valor pessoal: quanto mais se conhece a si mesmo, mais se olha para dentro de si, assim ao se olhar para dentro de si, fica fácil se colocar no lugar do outro. Ao fazer esse exercício, comete-se menos erro, portanto, a autoavaliação torna-se relevante por auxiliar o indivíduo na compreensão de si mesmo e na identificação das relações que mantém com as ações afetivas; quanto mais se liga ao mundo, melhor será a forma de se perceber como parte dele, ampliando sua visão de mundo e sociedade.…”
Section: Discussionunclassified
“…The 2019 instrument included 34 demographic questions. The demographic data were compared to Welsh and Blasch (1974), Uslan et al (1989), and Wiener and Siffermann (2000a) to determine trends and differences from the different years these studies reported.…”
Section: Methodsmentioning
confidence: 99%
“…Although the three studies used different methods to collect their data, it is possible to analyze comparable data among the studies to determine changes in the O&M profession between the earlier studies—Welsh and Blasch (1974), Uslan et al (1989), and Wiener and Siffermann (2000a)—and the current survey of O&M practitioners. Although not all of the questions were identical in all four studies, where possible, similar data were compared.…”
mentioning
confidence: 99%
“…The 1980s saw various developments in the basic concept of assistance cards for travelers who were deaf-blind, which had become the standard intervention in O&M (S. LaGrow, personal communication, August 16, 2006). In the first edition of Foundations of Orientation and Mobility (Welsh & Blasch, 1980), Lolli (1980, p. 444) provided an example of an assistance card that read, "Could you please help me to cross Maple Street?" (see Figure 1 for an example of an early assistance card).…”
Section: History Of and Literature On Assistance Gainingmentioning
confidence: 99%